Formação continuada sobre Aprendizagem Cooperativa para contemplar a diversidade em classes inclusivas - Costa, Pollyana Ladeia (2024)
This research is part of a matrix project entitled Collaborative action research to mitigate educational inequalities resulting from the COVID 19 pandemic: contributions from research on school inclusion (PAC-COVID 19), which involved a Program for Professional Development (PPD) organized into five modules, namely: 1) Collaborative Teaching and Inclusive School Culture; 2) Multitier System of Support (SSM); 3) Universal Design for Learning (UDL); 4) Differentiated Teaching Approach (ADT) and 5) Cooperative Learning (CL). The present work concerns module five of the PPD which dealt with Cooperative Learning. This is a research with a mixed methodological approach configured as collaborative action research. Considering the worsening of educational inequalities generated due the emergency remote teaching during the COVID 19 pandemic period, the general objective was to develop, implement and evaluate a Education Program (EP), based on the scientific literature of Cooperative Learning as an Inclusive Education strategy, in order to analyze whether the program offered contributes to providing teaching that better responds to the diversity of students at a target school. The specific objectives were: a) Develop the EP to contribute theoretical and practical knowledge about Cooperative Learning. b) Implement lesson plans based on Cooperative Learning, in classes from the 1st to the 3rd year of primary education at the target school, with the collaboration between class teachers and other EP participants. c) Evaluate the EP based on Cooperative Learning. The reflective critical epistemological core of the investigation was structured in Vygotsky 's historical-cultural approach. The study took place in a municipal public school in the interior of São Paulo, particularly in a Basic Education school, with 37 participants: regular teachers, special education teachers, educational coordinators and professionals from the multidisciplinary team. Furthermore, eight regular teachers applied the lesson plans basead on Cooperative Learning Theory with their 1st to 3rd year classroons of Elementary School. The EP was developed using a remote model, lasting 36 hours, whit synchronous and asynchronous activities. The results showed that the EP had positive impacts on the teachers and students involved, like for example, there were academic, psychological and social benefits for both, which allowed teachers to better respond to the diversity of students. In this way, the universalist and innovative practices such as Cooperative Learning, it enabled the professionals involved in EP to better confront educational inequalities caused by the COVID 19 pandemic in the school researched. Furthermore, in Brazil, the systematization of Cooperative Learning is still incipient, which the current work has contributed to produce evidences, and materials for continued education of teachers and to disseminate the theory in Brazil, that can foster inclusive education and research about Cooperative Learning.